Literary Criticism Aspect of Genre Way Analysis Application of Fictional Work in Professional Training of Future Teachers of Foreign Literature - Natalia Hrytsak (Pedagogical Discourse, 2018)
The present paper is focused on the literary criticism aspect of genre way analysis application of fictional work in professional training of future teachers of foreign literature. The problem of genre as literary criticism category, its components and structural content in the context of topical tendencies of modern genology is examined. Genre approaches, theories and conceptions of Y. Vasyliev, H. Yrabovych, N. Kopystianska, A. Tkachenko, T. Kushnirova and other scholars are studied. We have demonstrated the multivalence of this concept, content filling and specified characteristic features. “Genre” definition example that are included into the textbooks of modern Ukrainian authors on Introduction to literary criticism or Theory of Literature to the higher educational establishments have been provided in this work. Determination of the term content “genre” and its structure filling depends on scholars’ accents: form, content or synthesis of form and content. We draw our attention to the genre modifications and author’s genre nominations.  Key ideas concerning genre modifications of T. Bovsunivska, N. Tykholoz, S. Lenska have been emphasized. We emphasized that genre modifications assist genre renewal and development, broadening of genre potential, multifaceted coverage of the environment.Numeral growth of genre modifications is at the beginning of the XXI century as the limits of “pure” form of genre are erased. We have characterized that the problem of author’s genre definitions and emphasized less learning of this problem in modern genology. It has been revealed that in parallel with the scientific definition of the genre there is also the author's genre reflection, which is a reflection of author's worldview, author's genre searching, author's modification of the established features of the genre. We examine the communicative theory of J. Sheffer in the context of the problem of author’s genre definitions.